Physical activity and risk of gallstone disease: A Mendelian randomization study - Qian, Qilin; Jiang, Han; Cai, Bingyue; Chen, Dingwan; Jiang, Minmin (Frontiers in Genetics, 2022)
Objective: Given the association between physical activity and the reduced risk of gallstone disease as suggested in observational studies, a Mendelian randomization study was conducted to evaluate the causal nature of this association in genetic epidemiology. Study: Including self-reported and accelerometer-based physical activity traits, the independent genetic variants associated with physical activity were selected from the corresponding genome-wide association studies as instrumental variables. The summary-level data for gallstone disease were sourced from the UK Biobank (7,682 cases and 455,251 non-cases) and FinnGen consortium (23,089 cases and 231,644 non-cases). Then, two-sample Mendelian randomization analysis was conducted. Inverse-variance weight (IVW), weighted median, and Mendelian randomization–Egger regression were determined through Mendelian randomization analyses. To ensure the robustness of the results, sensitivity analyses were also carried out in the study. Results: The negative causality between the genetically predicted accelerometer-based “average acceleration” physical activity and the risk of gallstone disease was suggested in the UK Biobank study (p = 0.023, OR = 0.93, 95% CI: 0.87–0.99), and accelerometer-based “overall activity” physical activity and the risk of gallstone disease in the UK Biobank study (p = 0.017, OR = 0.38, 95% CI: 0.17–0.84). With accelerometer-based “average acceleration” physical activity negatively correlated with gallstone disease in the FinnGen consortium data (p = 0.001, OR = 0.94, 95% CI: 0.90–0.97). As for self-reported moderate-to-vigorous physical activity, however, there was no causality observed in both pieces of data. Conclusion: Our studies provide the evidence suggesting a casual association between physical activities and gallstone disease through analysis of genetic data. As indicated by the research results, there is a possibility that a higher level of physical activities could mitigate the risk of gallstone disease.